2002
DOI: 10.1002/sim.1358
|View full text |Cite
|
Sign up to set email alerts
|

Multicollinearity in prognostic factor analyses using the EORTC QLQ‐C30: identification and impact on model selection

Abstract: Clinical and quality of life (QL) variables from an EORTC clinical trial of first line chemotherapy in advanced breast cancer were used in a prognostic factor analysis of survival and response to chemotherapy. For response, different final multivariate models were obtained from forward and backward selection methods, suggesting a disconcerting instability. Quality of life was measured using the EORTC QLQ-C30 questionnaire completed by patients. Subscales on the questionnaire are known to be highly correlated, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
61
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(62 citation statements)
references
References 28 publications
1
61
0
Order By: Relevance
“…This is in line with reports that have indicated that the EORTC QLQ-C30 could be used for predicting survival as well as tumor response (39,40).…”
Section: Discussionsupporting
confidence: 91%
“…This is in line with reports that have indicated that the EORTC QLQ-C30 could be used for predicting survival as well as tumor response (39,40).…”
Section: Discussionsupporting
confidence: 91%
“…The stability of the final model was investigated using a bootstrap re-sampling procedure as proposed by Sauerbrei and Schumacher (1992), applied in the context of HRQOL (Van Steen et al, 2002). This technique generates a number of samples (each of the same size as the original data set), by randomly selecting patients and replacing them before selecting the next patient (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…11 For example, while "multicollinearity" is a known challenge in traditional PFA, it becomes even more problematic when PROs are included. 12 Multicollinearity occurs when two or more predictor variables are highly correlated (which is often the case for PROs) thus leading to incorrect model selection and, in any case, making it difficult to disentangle the real influence of each single predictor variable. 11,12 While there is still no gold standard to address this issue, some statistical techniques have been developed to further test the stability of the final multivariate predictive model and to obtain insight into the real value of a single factor being an independent prognostic variable.…”
mentioning
confidence: 99%
“…12 Multicollinearity occurs when two or more predictor variables are highly correlated (which is often the case for PROs) thus leading to incorrect model selection and, in any case, making it difficult to disentangle the real influence of each single predictor variable. 11,12 While there is still no gold standard to address this issue, some statistical techniques have been developed to further test the stability of the final multivariate predictive model and to obtain insight into the real value of a single factor being an independent prognostic variable. In the context of QoL studies, Van Steen et al 12 have extensively illustrated a bootstrap model averaging technique which was later successfully used in several methodologically sound studies of patients with solid tumors.…”
mentioning
confidence: 99%
See 1 more Smart Citation